PASSENGER SATISFACTION ON THE SERVICES PROVIDED BY HALIM PERDANA KUSUMA AIRPORT JAKARTA IN 2014 - Andri Andri; Suparwan Cecep Kosasih; Haryono Haryono (Institut Transportasi dan Logistik Trisakti, 2015)
Halim Perdana Kusuma International Airport is integrated with the development of National Economic Zones, which is included in the implementation of Master Plan for the Acceleration and Expansion of Indonesian Economic Development in Java and Sumatra islands. The operation of Halim Perdana Kusuma Airport is expected to become a locomotive for the economy of its surrounding regions because its presence will encourage the emergence of new centers of growth and economic activities. The operation of Halim Perdana Kusuma airport signifies the seriousness of the Indonesian government in preparing the accelerated development of national connectivity and supporting infrastructures in order to support the trade connectivity and it is projected to be national and regional aviation hub. Service is an act, performance appearance, intangible and it quickly disappears, which can only be consumed but can not be held, where customers can participate more actively in the process of consuming it. Assessment by customers on the performance of service providers will greatly influence the passenger satisfacti. If the passengers with a high level of importance or expectations find the airport performance comparable with their hope, thus it gives satisfaction to the passengers. Passenger satisfaction will have a positive impact on the airport, by which the airport sales volume will likely increase if the passengers' past experience as well as its word of mouth are positive.